1966
DOI: 10.1099/00221287-43-1-101
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Sulphate-reducing Bacteria by Fumarate Dismutation

Abstract: SUMMARYDesulfovibrio gigas and several strains of D. desulfwicans grew by fumarate dismutation in a sulphate-free medium. Two strains of D. desulfuricans grown in a chemically defined medium formed succinate, malate and acetate during fumarate dismutation. Sulphate reduction by these strains, though not by D. gigas, was almost completely inhibited in presence of fumarate as alternative electron acceptor. The anomalous behaviour of D. gigas was reflected to some extent by the hydrogen absorption coefficients fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 5 publications
2
12
0
Order By: Relevance
“…Growth on fumarate (Miller and Wakerley 1966) and malate (Miller et al 1970) was already reported for various Desulfovibrio strains. For each fumarate oxidized to acetate via malate and pyruvate, two fumarate molecules are reduced to succinate (Hatchikian and Le Gall 1970a, b;Hatchikian 1972).…”
Section: Discussionmentioning
confidence: 53%
“…Growth on fumarate (Miller and Wakerley 1966) and malate (Miller et al 1970) was already reported for various Desulfovibrio strains. For each fumarate oxidized to acetate via malate and pyruvate, two fumarate molecules are reduced to succinate (Hatchikian and Le Gall 1970a, b;Hatchikian 1972).…”
Section: Discussionmentioning
confidence: 53%
“…Malic enzyme, fumarase and acetate kinase were demonstrated also by their enzymic activities (Lewis & Miller, 1977;Brown & Akagi, 1966). Malate, which was suggested earlier as a product of fumarate disproportionation (Miller & Wakerley, 1966), apparently is only an intermediate. A similar form of fumarate disproportionation with succinate, acetate and CO 2 as the products was described for Clostridium formicoaceticum (Dorn et al, 1978), whereas fumarate disproportionation by Proteus rettgeri produced only succinate but no acetate (Kröger, 1974).…”
Section: Discussion Fumarate Respiration and Disproportionation By Sumentioning
confidence: 80%
“…Since C 4 compounds of the reductive TCA branch did not accumulate in I2 cultures, regardless of growth mode or electron donor (Table 2), we considered that I2 had altered fumarate metabolism. The growth of SRB by fumarate disproportionation has been described previously (53), where 3 fumarate ¡ 1 acetate ϩ 2 succinate ϩ 2 CO 2 . When G20 grown in lactate-sulfate was inoculated into fumarate medium, robust growth occurred after a lag (data not shown) and the expected primary end products of succinate and acetate accumulated in the predicted 2:1 ratio as the cells entered stationary phase (data not shown).…”
Section: Resultsmentioning
confidence: 99%